Drug Delivery: Gel–Liposome‐Mediated Co‐Delivery of Anticancer Membrane‐Associated Proteins and Small‐Molecule Drugs for Enhanced Therapeutic Efficacy (Adv. Funct. Mater. 16/2014). (April 2014) - Jiang, Tianyue; Mo, Ran; Bellotti, Adriano; Zhou, Jianping; Gu, Zhen
<x xml:space="preserve">Abstract</x> Sequential and site‐specific co‐delivery of two anticancer therapeutics in a programmed manner is demonstrated by J. Zhou, Z. Gu, and co‐workers on page 2295. The delivery is triggered by the tumor microenvironment and cellular conditions. The gel‐liposome based nanovehicle can transport and release an anticancer cytokine (TRAIL) and small‐molecule drug (doxorubicin) to their distinct acting sites: the cellular membrane and nucleus, respectively. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>